The species of the genus Plator Simon, 1880 in India (Araneae: Trochanteriidae) - Sankaran, Pradeep M.; Caleb, John T.d.; Sebastian, Pothalil A. (Zootaxa, 2020)
Plator species described in India are revised based on the type materials deposited in the National Zoological Collection, Zoological Survey of India, Kolkata. Five species are known in India, of which three are known only from females while the remaining two are from both sexes. All the type materials examined are imaged and redescribed.